Potensi Branding Keripik Pisang di Desa Sambirejo Kapanewon Ngawen Kabupaten Gunung Kidul - Dharomesz, Vonezyo Yupanzara (Jurnal Atma Inovasia, 2023)
Student Community Service is an activity in the form of community service that must be followed by every student at Atma Jaya University Yogyakarta. Student Community Service for the 2022 school year is conducted online with the theme Society 5.0. The group of 30 unit F Student Community Service Period 81 is located in Sambirejo Village, Ngawen District, Gunung Kidul Regency, Special Region of Yogyakarta. There is a lot of potential in Sambirejo village, one of which is the many banana tree plantations in Sambirejo village, and the bananas are used as processed foods in the form of banana chips. However, in marketing these products are less well known by the general public, therefore a work program is created which is implemented by making a branding on these processed foods and also conducting broader marketing using available electronic media so that these products can reach a wider range of consumers.